Legal Protection of Long Leave for Workers/Laborers Based on Law No. 6 of 2023 and Constitutional Court Decision No. 168/PUU-XXI/2023 (Lex Journal : Kajian Hukum dan Keadilan, 2025)
This study aims to analyze how the Legal Protection of the Right to Long Leave for workers according to Law Number 6 of 2023 and Constitutional Court Decision Number 168 / PUU- XXI / 2023 and to analyze Legal Considerations in Constitutional Court Decision Number 168 / PUU- XXI / 2023 have provided Legal Certainty and Justice for the Right to Long Leave for Labor / Workers. This type of research is normative legal research, normative legal research is also called doctrinal legal research and uses the Legislation approach, conceptual approach. Legal protection of long leave rights for certain time workers is regulated in Law Number 13 of 2003 concerning manpower and replaced by Law Number 6 of 2023 concerning Job Creation stating that long leave is entitled to be given to workers who have worked for 12 consecutive months or 1 consecutive year and at least 12 working days are given. The rules regarding long leave are further regulated in work agreements, company regulations or collective labor agreements. The legal protection of long leave for workers/laborers based on Law No. 6 of 2023 and Constitutional Court Decision No. 168/PUU-XXI/2023 in principle still refers to Article 79 paragraph (2) letter c of the Manpower Law, which states that leave arises after 12 months of continuous work. The Constitutional Court's decision does not change this provision, but focuses more on changes in the regulation of the term of the Fixed-Term Employment Agreement (PKWT) and the company's obligations regarding long breaks.